BOOK REVIEW The Best Weapon for Peace: Maria Montessori, Education and Children's Rights - Mira Catherine Debs (University of Kansas, 2022)
Erica Moretti, a professor of Italian at New York's Fashion Institute of Technology, authored a recent intellectual biography of Maria Montessori, The Best Weapon for Peace: Maria Montessori, Education, and Children's Rights. In this book, Moretti writes in conversation with fellow European researchers and builds on their work to present this English-language examination of Montessori's pacifism that places her as a central figure in 20th-century global humanitarianism, disaster relief, peace activism, and social reform.